2013
DOI: 10.1002/eji.201242819
|View full text |Cite
|
Sign up to set email alerts
|

Cellular‐FLIP, Raji isoform (c‐FLIPR) modulates cell death induction upon T‐cell activation and infection

Abstract: Dysregulation of apoptosis caused by an imbalance of pro-and anti-apoptotic proteinKeywords: Apoptosis r CD95 r c-FLIP r Listeria monocytogenes r T cells Introduction CD95 (Fas/APO-1)-induced apoptosis is an essential control mechanism of the immune system that protects the host against cancer and autoimmunity [1]. CD95 is a transmembrane receptor Correspondence: Dr. Ingo Schmitz e-mail: ingo.schmitz@helmholtz-hzi.de belonging to the tumor necrosis factor (TNF) receptor superfamily [2]. Binding of the cognate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…We previously reported that these transgenic mice have a better clearance of the Gram-positive bacteria Listeria monocytogenes compared with infected wild-type (WT) mice. 28 Here we show that aged mice constitutively expressing murine c-FLIP R have altered lymphocyte populations with higher levels of activated B and T cells compared with WT littermates. Moreover, vavFLIP R animals spontaneously develop autoimmunity with age, showing features of systemic lupus erythematosus (SLE).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…We previously reported that these transgenic mice have a better clearance of the Gram-positive bacteria Listeria monocytogenes compared with infected wild-type (WT) mice. 28 Here we show that aged mice constitutively expressing murine c-FLIP R have altered lymphocyte populations with higher levels of activated B and T cells compared with WT littermates. Moreover, vavFLIP R animals spontaneously develop autoimmunity with age, showing features of systemic lupus erythematosus (SLE).…”
mentioning
confidence: 64%
“…7, 30 c-FLIP R inhibits apoptosis by competing with caspase-8 for binding sites at the DISC. 17, 21 The mouse model vavFLIP R , in which murine c-FLIP R is under control of the vav -promoter to ensure expression in all hematopoietic compartments, 28 was used to study the functional role of murine c-FLIP R in the immune system. As thymocytes as well as B and T cells from vavFLIP R mice were protected against CD95-induced apoptosis, 28 we investigated if the impaired lymphocyte apoptosis in vavFLIP R mice would lead to elevated numbers of lymphocytes and altered lymphocyte populations with age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular FoxP3 expression was determined using the FoxP3 staining buffer kit (FJK-16s, eBioscience) according to the manufacturer’s recommendations. For apoptosis assay, Annexin/7AAD staining was performed as described previously [35]. Flow cytometric analysis was performed using a FACSCanto or LSRFortessa (BD Biosciences) running with THE FACSDiva software (version 6.1.3) (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…All the samples were run in triplicates. The results were obtained with FACS acquisition as described [35].…”
Section: Methodsmentioning
confidence: 99%